STRATEGI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MEWUJUDKAN TRANSFORMASI DIGITAL DAN BUDAYA INOVASI DI LEMBAGA PENDIDIKAN - Ayi Najmul Hidayat; Sobari Sobari; Ade Hernawan (Comm-Edu (Community Education Journal), 2026)
This research explores the life philosophy of the Miduana Indigenous community in Naringgul, Cianjur, as a form of enduring local wisdom. Through a qualitative case study, the research identifies how this community harmonizes Islamic teachings with ancestral Sundanese traditions. Key findings reveal that their "way of life" is integrated into ecological management, such as using traditional astronomy for farming and preserving "forbidden forests" (Leuweung Larangan). The study concludes that the resilience of Miduana’s culture amidst modernization is sustained by the moral authority of the Kasepuhan (elders) and early character education for the youth.